Evaluating the efficacy of the HITSystem 2.1 to improve PMTCT retention and maternal viral suppression in Kenya: Study protocol of a cluster-randomized trial. - Sharon Mokua; May Maloba; Catherine Wexler; Kathy Goggin; Vincent Staggs; Natabhona Mabachi; Nicodemus Maosa; Shadrack Babu; Emily Hurley; Sarah Finocchario-Kessler (PLoS ONE, 2022)
Background Gaps in the provision of guideline-adherent prevention of mother-to-child transmission of HIV (PMTCT) services and maternal retention in care contribute to nearly 8000 Kenyan infants becoming infected with HIV annually. Interventions that routinize evidence-based PMTCT service delivery and foster consistent patient engagement are essential to eliminating mother-to-child transmission of HIV. The HITSystem 2.1 is an eHealth intervention that aims to improve retention in PMTCT services and viral load monitoring, using electronic alerts to providers and SMS to patients. This study will evaluate the impact, implementation, and cost-effectiveness of HITSystem 2.1. Method This cluster randomized trial will be conducted at 12 study hospital (6 intervention, 6 control). Pregnant women living with HIV who have initiated PMTCT care ≤36 weeks gestation are eligible. Women enrolled at control hospitals will receive standard-of-care PMTCT services. Women enrolled at intervention hospitals will receive standard-of-care PMTCT services plus enhanced HITSystem 2.1 tracking. Mixed logistic regression models will compare the arms on two primary outcomes: (1) completed guideline-adherence PMTCT services and (2) viral suppression at both delivery and 6 months postpartum. We will assess associations between provider and patient characteristics (disclosure status, partner status, depression, partner support), PMTCT knowledge, and motivation with retention outcomes. Using the RE-AIM model, we will also assess implementation factors to guide sustainable scale-up. Finally, a cost-effectiveness analysis will be conducted. Discussion This study will provide insights regarding the development and adaptation of eHealth strategies to meet the global goal of eliminating new HIV infections in children and optimizing maternal health through PMTCT services. If efficacious, implementation and cost-effectiveness data gathered in this study will guide scale-up across Kenyan health facilities. Trial registration This study was registered at clinicaltrials.gov (NCT04571684) on October 1, 2020.